Effect of Surface Forces on Ultrathin Film Lubrication. (26th May 2014) - Mishra, Prakash Chandra
Abstract : Lubricated contact with nanoscale oil film is modeled for friction. Effect of the van der Waals pressure and the solvation pressure forces on such ultrathin lubricating oil film is considered while finding the friction and other parameters. Hydrodynamic action is represented using transient thermoelastohydrodynamics. Net pressure due to hydrodynamic, solvation, and van der Waals' action is integrated over the contact area to find contact load. Conjunctional friction due to thermal activation of such ultrathin film is derived using the Eyring model. Effect of molecular dimension on friction is studied.